Analisis Pengaruh Task Characteristics, Technology Characteristics, Task–Technology Fit, Intrinsic Motivation, Dan Extrinsic Motivation Terhadap Usage Behavior Aplikasi Strava - Hendrik Susilo; Ghea Sekar Palupi (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The rapid growth of digital fitness applications has increased the use of technology to support physical activities, one of which is through the Strava application. However, sustaining user engagement remains a challenge, as not all users maintain long-term usage intensity. This study aims to analyze the factors influencing the usage behavior of Strava users by integrating the Task–Technology Fit (TTF) model and Self-Determination Theory (SDT). The research was conducted through several stages, including problem identification, literature review, conceptual model and hypothesis development, instrument design, pilot testing, data collection, and data analysis using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. Data were collected from 200 active Strava users in Surabaya, Indonesia, selected through purposive sampling. The results indicate that Task Characteristics and Technology Characteristics have a positive and significant effect on Task–Technology Fit. Furthermore, Task–Technology Fit positively and significantly influences both Intrinsic Motivation and Usage Behavior. In addition, Intrinsic Motivation and Extrinsic Motivation are found to have positive and significant effects on Usage Behavior, with Intrinsic Motivation demonstrating a stronger influence. This study concludes that the alignment between technological capabilities and users’ activity needs, along with user motivation, plays an important role in encouraging the continued use of the Strava application.